2014
DOI: 10.1098/rspb.2014.1461
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of phylogeographic endemism in an environmentally complex biome

Abstract: Phylogeographic endemism, the degree to which the history of recently evolved lineages is spatially restricted, reflects fundamental evolutionary processes such as cryptic divergence, adaptation and biological responses to environmental heterogeneity. Attempts to explain the extraordinary diversity of the tropics, which often includes deep phylogeographic structure, frequently invoke interactions of climate variability across space, time and topography. To evaluate historical versus contemporary drivers of phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
268
2
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 256 publications
(296 citation statements)
references
References 52 publications
19
268
2
7
Order By: Relevance
“…A recent large-scale biogeographic study of T. taophora and its sister species T. miliaris showed high levels of phylogenetic diversification in these species likely due to past climatic oscillations, topographic complexity and the heterogeneity of habitats in the Atlantic Coastal Forest (Fitzpatrick et al, 2009;Carnaval et al, 2014). That study found that populations in Juréia were genetically isolated and diverged early in the history of remaining T. taophora populations (Fitzpatrick et al, 2009).…”
Section: Population Structure and Implications For Diversificationmentioning
confidence: 77%
“…A recent large-scale biogeographic study of T. taophora and its sister species T. miliaris showed high levels of phylogenetic diversification in these species likely due to past climatic oscillations, topographic complexity and the heterogeneity of habitats in the Atlantic Coastal Forest (Fitzpatrick et al, 2009;Carnaval et al, 2014). That study found that populations in Juréia were genetically isolated and diverged early in the history of remaining T. taophora populations (Fitzpatrick et al, 2009).…”
Section: Population Structure and Implications For Diversificationmentioning
confidence: 77%
“…CD and BCF are historical refuges for plants in two different floristic domains. CD is considered a refuge for grasslands during interglacial periods (e.g., [34,67,68]) or for firesensitive lineages after the expansion of the fire-prone Cerrado in Central Brazil [36,66], whereas BCF is a refuge for forest associated lineages [40]. These plant refuges shelter an exceptionally high PD, which is phylogenetically clustered in CD but overdispersed in BCF.…”
Section: Discussionmentioning
confidence: 99%
“…It is floristically influenced by seasonally dry forests from the surrounding Caatinga but is also home of palaeomicroendemics [35] and was recently postulated as a historical refuge for fire-sensitive lineages [36]. The Bahia Costal Forest (BCF) ecoregion [37] is the largest area of climatic stability in the northern block of the Atlantic Forest [38][39][40]. Ranging from northern Espirito Santo to southern Bahia, it is dominated by evergreen forests, harbouring a forest refuge, with high levels of endemism [41] and one of the highest tree species densities in the world [42].…”
Section: Introductionmentioning
confidence: 99%
“…Models of the paleodistribution of the species were derived with snapshot simulations of climate spanning the last 70 ky (at 1-ky time intervals back up to 22 kya, and before that at 2-ky time intervals, with 46 time periods in total) derived from the Hadley Centre Climate model (HadCM3) (50,51). To project species ranges and genetic diversity under future climates, we used bioclimatic variables estimated from the Hadley Center model for the years 2030, 2050, 2070, and 2080 (HadGEN2-ES) (32), which is based on the RCP 6.0 emission scenario (31).…”
Section: Methodsmentioning
confidence: 99%